"I've got something to tell you. I'm dyslexic": The lived experiences of trainee teachers with dyslexia. (August 2021) - Jacobs, Lisa; Collyer, Edward; Lawrence, Clare; Glazzard, Jonathan
Abstract: Literature has explored the placement experiences of primary school trainee teachers with dyslexia but there is a scarcity of research on secondary school trainees or university-based experiences. This study examined the experiences of three primary and four secondary school trainees with dyslexia, encompassing both their university and placement-based experiences in England. This research highlighted the similarities in experience across training in a primary and a secondary school but found there are specific challenges associated with training to teach at secondary school level. We also captured the strengths trainees brought to the profession. Implications for initial teacher education providers are discussed. Highlights: Secondary school trainees with dyslexia have unique experiences. Trainee teachers with dyslexia bring strengths to the profession. University based challenges include lectures and accessing learning support. Placement based challenges include marking and unsupportive mentoring.